Effect of Rainfall Kinetic Energy on Crust Formation and Interrill Erosion of an Ultisol in Subtropical China. Issue 4 (13th September 2013) - Zhou, Hu; Peng, Xinhua; Darboux, Frédéric
Abstract : Rainfall kinetic energy plays an important role in breaking down aggregates and forming crusts. A laboratory rainfall simulation study was conducted on an Ultisol from subtropical China to investigate the effect of rainfall kinetic energy on crusting, infiltration, runoff, and erosion. Two treatments, that is, high kinetic energy (HKE) and low kinetic energy (LKE), were applied during this study. Air‐dried soil was packed in a soil box (50 by 50 cm), and the soil box was subjected to 38 mm h −1 rainfall with three replicates. The runoff, splash, erosion, and percolation were measured during the simulation. For each treatment, an additional soil box was dedicated to sampling the undisturbed soil samples at different time intervals to make thin sections. The entire soil surface was covered by structural or sedimentary crust at the end of the experiment. When compared with the HKE rainfall, the LKE rainfall reduced the direct physical impact of raindrops that disintegrated the soil aggregates and compacted the soil surface; therefore, the LKE preserved the soil infiltration capability and subsequently postulated the formation of crust. This resulted in a higher infiltration rate and greater cumulative infiltration and percolation but lower splash, runoff, and soil erosion in the LKE treatment compared with the HKE treatment. The results show that Ultisols are prone to crusting and that rainfall kinetic energy is a major driver of crust formation. This finding indicates that mulching the soil surface is an effective way to alleviate crusting, to conserve more water, and to reduce erosion.